Edukasi Menstruasi di Pondok Pesantren dan Lembaga Kesejahteraan Sosial Anak (LKSA) Bintaan Sa'adillah Ar Rosid Krapyak - Yati, Dwi (ABDIMAS Madani, 2022)
Menstruation is vaginal bleeding that occurs periodically due to the shedding of the endometrial lining of the uterus. Menstruation is often followed by various complaints, including pain during menstruation, cycle disturbances, blood volume during menstruation and menstrual hygiene. Most teenagers get information related to menstruation from her friends, so that the information obtained is not necessarily true and good quality. The purpose of this community service is to increase the knowledge of Islamic boarding school teenagers on problems related to menstruation and how to solve them. The method used in the form of counseling and video playback. The results obtained are 80% of respondents received information related to menstruation.64% got the information from friends. The level of knowledge of respondents before being given education was mostly 64% in the poor category, and after receiving counseling 100% in the good category. The conclusion in this community service is that there is an increase in the knowledge of the teenagers of the Islamic boarding school & LKSA Bintaan Sa'adillah Ar Rosid Krapyak Wetan after providing education about menstruation.